PHYSICOCHEMICAL STUDY OF THERMOPLASTIC STARCH(TPS) USING IONIC LIQUID AS PLASTICIZER - MALKEET SINGH, JASPREET KAUR SIDHU (IRC, 2017)
This research investigates the physicochemical and hygroscopic properties of thermoplastic starch (TPS) an alternative biodegradable material. The material is formed from starch, Ionic liquid (IL) as plasticizer and rice straw fibre (RS) as fillers. TPS is synthesised through starch gelatinization process with the presence of plasticizer at elevated temperature. For this study, two types of ionic liquids as plasticizer are compared which are 1-ethyl-3-methylimidazolium acetate [Emim]Ac and 1-ethyl-3-methylimidazolium chloride [Emim]Cl. The best plasticizer will be chosen through thermal analysis by using Differential Scanning Calorimetry (DSC) and Thermal Gravimetric Analysis (TGA). From the result, it was found that [Emim]Ac was the better plasticizer. Following towards the second focus of this study which is to investigate the physicochemical properties and the moisture absorption rate of the synthesised TPS. The optimised TPS will be mixed with RS which aims to reduce moisture uptake. From the moisture absorption analysis, it was found that, 40% of RS loading showed the lowest moisture absorption rate for both 50% and 75% relative humidity (RH). Whereas, the FTIR results indicated that there is new bond formation in the synthesised TPS as well as TPS mixed with RS. SEM images clearly shows the interaction between the TPS samples. In addition, the TPS that is formed is more amorphous compared to other samples. The thermal analysis, showed that the TPS synthesised is thermally stable which includes TPS with 40% RS loading. The biodegradability test also proved that indeed [Emim]Ac can withstand microbial attack. The results obtained clearly showed there is a good potential to use [Emim] Ac and RS as plasticizer and fillers respectively to synthesise an alternative biodegradable material.